The Role of Music and Songs in Teaching English as a Foreign Language - Dezső Nóra (2000)
In my thesis I am trying to examine the possibilities of using more music in foreign language teaching. Firstly, a review of the literature that gave me a motivation for writing about this theme will be given. Then the results of a survey done in two elementary schools in Hódmezővásárhely will be analysed in order to give an overall picture about how students feel about music and how teachers put music into English lessons. I suppose that students in the elementary music school listen to more music on foreign language lessons than the ones who are not specialized in this subject. Finally, I would like to mention some types of songs, their usabilities and my experiences in teaching.